2022
DOI: 10.3390/ijms23126489
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Mutated Non-Small Cell Lung Cancer and Resistance to Immunotherapy: Role of the Tumor Microenvironment

Abstract: Lung cancer is a leading cause of cancer-related deaths worldwide. About 10–30% of patients with non-small cell lung cancer (NSCLC) harbor mutations of the EGFR gene. The Tumor Microenvironment (TME) of patients with NSCLC harboring EGFR mutations displays peculiar characteristics and may modulate the antitumor immune response. EGFR activation increases PD-L1 expression in tumor cells, inducing T cell apoptosis and immune escape. EGFR-Tyrosine Kinase Inhibitors (TKIs) strengthen MHC class I and II antigen pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 103 publications
0
40
0
Order By: Relevance
“…EGFR -mutant NSCLC cases are reported to “immune cold” relative to other cases because of multiple alterations in the tumor cells per se e.g., increased PD-L1 expression but also because of changes in the tumor microenvironment [19]. PD-L1 is also reported in EVs from NSCLC cells including those with EGFR-mutations and as a next step in our analyses we therefore studied heterogeneity in PD-L1 expression in EVs isolated from cell culture media of H1975 cells prior and post EGFR-TKI treatment [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR -mutant NSCLC cases are reported to “immune cold” relative to other cases because of multiple alterations in the tumor cells per se e.g., increased PD-L1 expression but also because of changes in the tumor microenvironment [19]. PD-L1 is also reported in EVs from NSCLC cells including those with EGFR-mutations and as a next step in our analyses we therefore studied heterogeneity in PD-L1 expression in EVs isolated from cell culture media of H1975 cells prior and post EGFR-TKI treatment [18].…”
Section: Resultsmentioning
confidence: 99%
“…By combining the results from the numerical data with the intensities it seems like the EVs isolated post EGFR-TKI treatment are more positive to PD-L1, but with reduced number of proteins per vesicle. As it has been demonstrated in other tumor types that PD-L1 expressing EVs may block effect of ICI treatment it is interesting to note that PD-L1 alterations occur on EVs after EGFR-TKI which may indeed contribute to the observed immune cold phenotype of EGFR-mutant NSCLC cases [29], [19], [38], [39], [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies also reported that the responsiveness or tolerance to immunotherapy was significantly related with tumor mutations ( 43 , 44 ). Thus, we analyzed the mutation profiles and found that the TMB between C1 and C2 was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not compare the TMB levels according to EGFR mutational status, our study confirmed previous findings of relatively low TMB levels in EGFR -positive tumors. Evidence indicates that ICIs are not effective in the oncogene-driven lung cancers, and it is partly due to an immunosuppressive tumor microenvironment (TME) in such tumors, including the recruitment of tumor-associated macrophages and regulatory T-cells and the production of inhibitory cytokines that are induced by the activated EGFR signaling [ 23 ]. TMB represents the mutational load in the tumor cell genome and serves as a surrogate marker for tumor neoantigen production and potential immunogenicity.…”
Section: Discussionmentioning
confidence: 99%